2013
DOI: 10.5812/jjm.5453
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effect of Zataria multiflora Extract on Methicillin Resistant Staphylococcus aureus

Abstract: Background:One of the most common nasocomial bacteria is methicillin resistant Staphylococcus aureus (MRSA). Today, herbal extracts like Zataria multiflora from the Lamiaceae family are increasingly used. Objectives: In this study, the antibacterial effect of Z. multiflora on 75 strains of was evaluated. Materials and Methods:The strains of Staphylococcus aureus were examined for isolation of strains. 75 out of 232 strains were diagnosed as by oxacillin 6µg /mL screening method. The extracts of Z. multiflora w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Many minor skin infections (i.e., localized infections) caused by S. aureus can be treated with topical agents such as mupirocin and retapamulin; however, most MRSA strains are resistant to these and other conventional antibiotics. Cationic AMPs and their synthetic derivatives are promising candidates to combat antibiotic resistance ( 8 , 20 , 21 ). We investigated the wound-healing efficacy of CM11, a short hybrid cationic peptide, against S. aureus skin infection.…”
Section: Discussionmentioning
confidence: 99%
“…Many minor skin infections (i.e., localized infections) caused by S. aureus can be treated with topical agents such as mupirocin and retapamulin; however, most MRSA strains are resistant to these and other conventional antibiotics. Cationic AMPs and their synthetic derivatives are promising candidates to combat antibiotic resistance ( 8 , 20 , 21 ). We investigated the wound-healing efficacy of CM11, a short hybrid cationic peptide, against S. aureus skin infection.…”
Section: Discussionmentioning
confidence: 99%
“…ZM is chemically similar to T. vulgaris, and its leaf is listed in the Herbal Pharmacopoeia (15). Many studies have demonstrated the antibacterial and anti-inflammatory effects of ZM extract (16)(17)(18)(19) though there are inconclusive results about ZM products used for the relief of gastrointestinal syndromes, few studies have been carried out on the antitussive effects of this indigenous plant (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the MIC of ZMB extract for the standard strain was 10 µg/mL and for the clinical isolate it was 25 µg/mL, as compared with commercial antibiotics (Table ). Similar results showed that the alcoholic extract of ZMB at low concentrations could inhibit the growth of gram‐positive bacteria . In kinetic assays, Montagu et al showed that carvacrol had a bacteriostatic effect at 3 hours and a bactericidal effect from 6 to 24 hours.…”
Section: Discussionmentioning
confidence: 73%
“…Similar results showed that the alcoholic extract of ZMB at low concentrations could inhibit the growth of gram-positive bacteria. 19,20 In kinetic assays, Montagu et al 21 showed that carvacrol had a bacteriostatic effect at 3 hours and a bactericidal effect from 6 to 24 hours. Furthermore, Eftekhar et al 22 reported that ZMB essential oil had considerable in vitro activity against the standard ATCC cultures, as well as the clinical isolates of K. pneumonia.…”
Section: Discussionmentioning
confidence: 99%